Apremilast for the treatment of moderate‐to‐severe palmoplantar psoriasis: results from a double‐blind, placebo‐controlled, randomized study. (15th November 2017) - Bissonnette, R.; Haydey, R.; Rosoph, L.A.; Lynde, C.W.; Bukhalo, M.; Fowler, J.F.; Delorme, I.; Gagné‐Henley, A.; Gooderham, M.; Poulin, Y.; Barber, K.; Jenkin, P.; et al.
Abstract: Background: Palmoplantar psoriasis is a variant of psoriasis vulgaris which can severely impair quality of life. Objectives: The main objectives of this double‐blind, placebo‐controlled, randomized study were to assess the efficacy and impact on quality of life and work productivity of apremilast for the treatment of moderate‐to‐severe palmoplantar psoriasis. Methods: A total of 100 patients with moderate‐to‐severe palmoplantar psoriasis were randomized to either apremilast 30 mg bid or placebo for 16 weeks. At Week 16, all patients received apremilast 30 mg bid until Week 32. The primary endpoint was the proportion of patients who achieved a Palmoplantar Psoriasis Physician Global Assessment (PPPGA) of 0/1 at Week 16. Results: There was no significant difference in the proportion of patients who achieved a PPPGA of 0/1 at Week 16 between patients randomized to apremilast (14%) and placebo (4%; P = 0.1595). After 32 weeks of treatment with apremilast, 24% of patients achieved a PPGA of 0/1. In addition, apremilast was superior to placebo in achieving Palmoplantar Psoriasis Area Severity Index (PPPASI) 75 (apremilast: 22%; placebo: 8%; P = 0.0499), in improving PPPASI (apremilast: −7.4 ± 7.1; placebo: −3.6 ± 5.9; P = 0.0167), Dermatology Life Quality Index score (apremilast: −4.3 ± 5.1; placebo: −0.8 ± 4.5; P = 0.0004) and in reducing activity impairment (apremilast: −11.0 ± 22.3; placebo: 2.5 ± 25.5; P = 0.0063). Conclusion: Despite the absence of a significant difference between apremilast and placebo in proportion of patients achieving a PPPGA of 0/1, the presence of significant differences observed for several secondary endpoints suggests that apremilast may have a role in the treatment of moderate‐to‐severe palmoplantar psoriasis.